Eksplorasi Pemikiran Heidegger: Teknologi dan Keterasingan Dalam Masyarakat Modern - Fakhrurrozi, M Rifqi; ., Wawaysadhya (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2024)
In recent decades, global society has experienced profound changes due to rapid technological advances. One thinker who has deeply explored the impact of technology on humans is Martin Heidegger. This study aims to examine how Heidegger's thoughts on technology and alienation in contemporary phenomena. The data collection technique uses analytic content, namely tracing various sources of literature and literature that are relevant to Martin Heidegger's thoughts on technology and alienation. The data sources used consist of books, articles, journals and previous research results. Data processing and analysis techniques are carried out by collecting data, in-depth analysis, evaluating data, presenting data, validating data and finally drawing conclusions. The results of the study show that Heidegger's thoughts on technology and alienation are still very relevant in the context of modern society. Heidegger provides a strong philosophical framework for understanding how technology shapes and limits human experience, and how to find solutions to overcome its negative impacts. Heidegger reminds us that technology is not a neutral entity, but something that shapes the way humans understand and interact with the world.